Isoginkgetin increases the expression of metal responsive transcripts but inhibits their translation - Claire Peneycad; Erin van Zyl; Abhinav Mohur; Bruce C. McKay (PLoS ONE, 2026)
Isoginkgetin (IGG) is a natural bioflavonoid isolated initially from leaf extracts of Gingko biloba trees used in traditional Chinese medicine. We previously reported that IGG strongly inhibits nascent protein synthesis by activating the shared ATF4-dependent branches of the integrated stress response (ISR) and the unfolded protein response (UPR). Here we sought to characterize an ATF4-independent response to IGG that leads to increased expression of mRNAs encoding metallothionines (MTs) and a zinc transporter (ZnT1). We confirm that IGG induces MT1F, MT1X, MT2A and ZnT1 mRNAs in several independent cell lines. We also find that siRNA-mediated knockdown of the metal regulatory transcription factor 1 (MTF-1) reduced basal and IGG-induced levels of these mRNAs. Curiously, we did not detect increased expression of these proteins following exposure to IGG. To study the dissociation between transcription and translation of metal responsive mRNAs, we created a stable cell line expressing a luciferase reporter gene under control of five metal response elements. Our positive control (ZnSO 4 ) increased luciferase activity as expected but IGG reduced luciferase activity. Importantly, IGG, and other inhibitors of translation, prevented the increase in luciferase activity when combined with ZnSO 4 without affecting the ZnSO 4 -induced increase in luciferase mRNA levels. We propose that IGG activates ATF4- and MTF-1-dependent transcriptional responses but that IGG simultaneously impairs nascent protein synthesis and masks the metal response at the protein level.